Flores conversam no jardim: movimentos do cuidado de si por mulheres em tratamento no caps ad (CPTT) na reinvenção de suas vidas - Rasch, Scheila Silva (2014)
Historically drug use by women was renegade, hidden prejudices and social stigmas. Research and therapeutic undertaken for men were imposed on women, disregarding their singularities. This thesis aims to reduce that gap and gap, in order to analyze the movements of self-care for women undergoing treatment at the Center for Psychosocial Care Alcohol and Drugs, the Center for Prevention and Treatment of drug addicts in Vitória / ES. Using qualitative-clinical, with Reich's approach and neorreichiano articulated body psychotherapies with the wording of Comprehensive Care Policy on Alcohol and Other Drugs Use and the like, the study included the participation of 27 women. Data were collected at the Women's Group, to understand the movements of self-care, and were analyzed by thematic analysis technique, while data collected from medical records to understand the unique therapeutic project and the use of network services have been described for identification of the women's characteristics. The results showed the invention of expansive movements such as treatment, the defense of life, the social rehabilitation and the resumption of female roles; and contraction movements as social exclusion, family, discrediting the change and treatment, codependency, risks and vulnerabilities by women. We conclude that the expansion moves repositioned women in relation to the drug and in other walks of life, and that the contraction movements reaffirmed the condition of drug users, who want to overcome condition when it come to care for oneself.